Nomenclatural notes on Eugenia section Phyllocalyx (Myrtaceae) - Bünger, Mariana De Oliveira; Mazine, Fiorella Fernanda; Stehmann, João Renato (Phytotaxa, 2016)
Eugenia Linnaeus (1753: 470) is a widespread tropical genus with about 385 species in Brazil (Govaerts et al. 2014, Sobral et al. 2016), most of which grow in the Brazilian Atlantic rainforest biome (Oliveira-Filho & Fontes 2000). This richness, allied to the fact that some species are known from a single historical collection, perhaps a specimen with only fruits or only flowers, results at times in considerable taxonomic uncertainty, making it difficult to identify specimens with any level of confidence (Landrum & Kawasaki 1997: 509).